Increased Serum Brain-derived Neurotrophic Factor, Nerve Growth Factor, Glial-derived Neurotrophic Factor and Galanin Levels in Children with Attention Deficit Hyperactivity Disorder, and the Effect of 10 Weeks Methylphenidate Treatment - Gumus, Cavithan; Yazici, Ipek Percinel; Yazici, Kemal Utku; Ustundag, Bilal (Korean Coll Neuropsychopharmacology, 2022)
Objective: This study aimed to investigate the levels of serum brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), glial cell-derived neurotrophic factor (GDNF) and galanin in children with attention deficit hyperactivity disorder (ADHD).Methods: The study included 58 cases with ADHD and 60 healthy controls. Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime version (K-SADS-PL) together with Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5) criteria were used for diagnostic evaluation. Sociodemographic data form and Conners' Parent/Teacher Rating Scale-Revised:Long Form were applied to all cases. The serum levels of BDNF, NGF, GDNF, and galanin were evaluated in all subjects. Afterwards, methylphenidate was started in the ADHD group. ADHD cases were reevaluated in terms of the serum levels of BDNF, NGF, GDNF, galanin at the 10th week of treatment.Results: Before the treatment, the levels of BDNF, NGF, GDNF, galanin were significantly higher in the ADHD group compared to the control group. The levels of BDNF, NGF, GDNF, galanin were found to be significantly lower after treatment in ADHD group compared to pre-treatment. No correlation was between scale scores and the serum levels of BDNF, NGF, GDNF, galanin. Conclusion: The levels of neurotrophic factors and galanin were thought to be parameters worth evaluating in ADHD. Further studies on the subject with longer-term treatments and larger sample groups are required.
Keywords: Attention deficit hyperactivity disorder; BDNF; NGF; GDNF; Galanin; Methylphenidate